Microeconomic Flexibility in Latin America - Ricardo J. Caballero; Eduardo M.R.A. Engel; Alejandro Micco (Yale University, Economic Growth Center, 2004)
We characterize the degree of microeconomic inflexibility in several Latin American economies and find that Brazil, Chile and Colombia are more flexible than Mexico and Venezuela. The difference in flexibility among these economies is mainly explained by the behavior of large establishments, which adjust more promptly in the more flexible economies, especially when accumulated shocks are substantial. We also study the path of flexibility in Chile and show that it declined in the aftermath of the Asian crisis. This decline can account for a substantial fraction of the large decline in TFP-growth in Chile since 1997 (from 3.1 percent per year for the preceding decade, to about 0.3 percent after that). Moreover, if it were to persist, it could permanently shave off almost half of a percent from Chile's structural rate of growth.
Keywords: E2; J2; J6; 330; Microeconomic rigidities; creative-destruction; job flows; restructuring and reallocation; productivity growth; Arbeitsproduktivität; Anpassungskosten; Lateinamerika; Flexibilität; Grenzkosten